2022
DOI: 10.1609/icwsm.v16i1.19281
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Political Polarization in the Vaccination Stance: The Brazilian COVID-19 Scenario

Abstract: The outbreak of COVID‐19 had a huge global impact, and non-scientific beliefs and political polarization have significantly influenced the population's behavior. In this context, COVID vaccines were made available at an unprecedented time, but a high level of hesitance has been observed that can undermine community immunization. Traditionally, anti-vaccination attitudes are more related to conspiratorial thinking than political bias. In Brazil, a country with an exemplar tradition in large-scale vaccination pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
10
0
3
Order By: Relevance
“…Trust and safety-related topics, for example, side effects, rushed vaccine, featured prominently in the antivax tweets, which supports other work that identified safety and trust (in institutions and governments) as a key hurdle in addressing vaccine hesitancy [18,20,23]. Our stance detection approach also enabled the definitive identification of a set of dual-stance users who contributed a significant volume to both antivax and provax tweets, supporting existing findings [4,26,[119][120][121]133].…”
Section: Comparison With Prior Worksupporting
confidence: 81%
See 1 more Smart Citation
“…Trust and safety-related topics, for example, side effects, rushed vaccine, featured prominently in the antivax tweets, which supports other work that identified safety and trust (in institutions and governments) as a key hurdle in addressing vaccine hesitancy [18,20,23]. Our stance detection approach also enabled the definitive identification of a set of dual-stance users who contributed a significant volume to both antivax and provax tweets, supporting existing findings [4,26,[119][120][121]133].…”
Section: Comparison With Prior Worksupporting
confidence: 81%
“…A growing body of literature has analyzed social media posts, particularly tweets related to COVID-19 vaccines. Here, we compared our work with 29 significant Twitter studies [2][3][4][5][6][7]18,20,21,[23][24][25][26][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Unsupervised methods, such as sentiment analysis and topic modeling, are the most popular methods used to classify and analyze tweets; 11 studies used some combination of sentiment analysis, emotion analysis, and topic modeling [3,6,20,21,24,124,126,128,130,131,134].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…While further research is necessary, such a link has been confirmed in some studies. For example, attitudes toward COVID-19 vaccination in Brazil, a country of strong internal conflicts, have been associated with political polarisation [ 80 ]. Moreover, Brazil is also a country where trust in the government is low [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a substantial amount of work studying public behaviour towards COVID-19 vaccines since the beginning of the pandemic. These papers have looked at the issue from various angles, such as, discovering the leading factors behind vaccine hesitancy [2]- [4], [10]- [13], correlation between political polarisation and vaccine stance [14], coordinated behaviour in propagation of misinformation [15], etc. They also have used a broad range of techniques to classify tweets as pro-vax or anti-vax, such as, unsupervised learning methods of sentiment analysis and topic modelling or supervised learning techniques where a subset of tweets, hashtags, or users are labelled by annotators and the labels are used to automatically detect stances for tweets or users.…”
Section: Related Workmentioning
confidence: 99%